2021
DOI: 10.3389/fimmu.2021.607315
|View full text |Cite
|
Sign up to set email alerts
|

IL10- and IL35-Secreting MutuDC Lines Act in Cooperation to Inhibit Memory T Cell Activation Through LAG-3 Expression

Abstract: Dendritic cells (DCs) are professional antigen-presenting cells involved in the initiation of immune responses. We generated a tolerogenic DC (tolDC) line that constitutively secretes interleukin-10 (IL10-DCs), expressed lower levels of co-stimulatory and MHCII molecules upon stimulation, and induced antigen-specific proliferation of T cells. Vaccination with IL10-DCs combined with another tolDC line that secretes IL-35, reduced antigen-specific local inflammation in a delayed-type hypersensitivity assay indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 37 publications
3
11
0
Order By: Relevance
“…We have previously shown that anti-TNF reduced the activated CD4 + CD25 + T cells derived from PBMCs of PsA patients in vitro [35]. These findings were consolidated with recently published reports demonstrating that LAG-3 inhibited CD4 + T cell activation [36] and that LAG-3 was up-regulated in the reduced activated cells [37]. The mechanisms proposed for anti-TNF ability to increase T regs function are through FoxP3 mRNA and protein up-regulation and restoration of suppressive function through TNF receptor 2 on T regs [38].…”
Section: Discussionsupporting
confidence: 71%
“…We have previously shown that anti-TNF reduced the activated CD4 + CD25 + T cells derived from PBMCs of PsA patients in vitro [35]. These findings were consolidated with recently published reports demonstrating that LAG-3 inhibited CD4 + T cell activation [36] and that LAG-3 was up-regulated in the reduced activated cells [37]. The mechanisms proposed for anti-TNF ability to increase T regs function are through FoxP3 mRNA and protein up-regulation and restoration of suppressive function through TNF receptor 2 on T regs [38].…”
Section: Discussionsupporting
confidence: 71%
“…Evidence shows a decreasing arthritis index, and promoting apoptosis in CIA mice, which is injected with IL-35 intraperitoneally ( Li et al, 2016b ). Moreover, by upregulating the secretion of IL-35, it is found that IL-35 reduces antigen-specific local inflammation and impaired disease development of RA in CIA mice ( Yin et al, 2016 ; Koga et al, 2021 ). Besides, the antagonist of IL-35 is injected into the joint space and exerted the highest anti-inflammatory effects ( Abdi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…We included WT DCs and IL-10-secreting DCs (IL-10 DCs) as immunogenic and tolerogenic DC models, respectively (Figure a). The tolerogenic features of IL-10 DCs were previously characterized by significant downregulation of stimulatory surface markers such as MHC-II, CD40, CD80, and CD86 compared to WT DCs upon stimulation . Additionally, we used the B16 melanoma line (B16) as a tumor cell model that expresses PD-L1 to investigate how the blocking efficacy compares to DCs, as tumor cells are known to inhibit immune activation (Figure a).…”
Section: Resultsmentioning
confidence: 99%